Hubungan keterampilan bertanya guru dengan hasil belajar kognitif IPAS materi cerita tentang daerahku kelas IV SD - Indah Permatasari; Sandra Bayu Kurniawan (Didaktika Dwija Indria, 2025)
Thoughtful questioning by teachers is essential for fostering students' critical thinking skills and actively involving them in the learning process. This study aims to determine the relationship between teacher questioning skills and cognitive learning outcomes in IPAS topic "Stories About My Region" of grade IV elementary school students in Pedan district for the 2024/2025 academic year. This study adopted a quantitative methodology, incorporating an ex post facto design and correlational analysis. Data were collected using a Guttman scale questionnaire for teacher questioning skills and an essay test for IPAS cognitive learning outcomes. We obtained a sample of 67 students from the elementary school of Muhammadiyah Al-Bayyin, elementary school of 1 Keden, and elementary school of 1 Ngaren was selected using cluster random sampling. The analysis used point biserial correlation and simple linear regression tests. The findings indicated a significant positive correlation (p = 0.041, r = 0.250), although categorized as low. Teacher questioning skills also significantly influenced students' cognitive learning outcomes ( = 0.063). Teachers who are skilled at asking questions tend to foster greater cognitive development in their students. This finding implies that improving teacher questioning skills, especially in advanced questioning techniques and providing sufficient thinking time, is necessary to optimize student learning outcomes.